Competence Profiling for Loans Officers in the Banking Sector in Sub-Saharan Africa: A Case of Uganda - Kasekende, Francis; Munene, John C. (CAPA Scientific Journal, 2014)
This paper examined the operant competences for bank loans officers in a Sub-Saharan context and provided policy input required in solving the daunting problem of the existing low levels and high failure rate of collecting loans disbursed to customers. Data were collected from a sample of 319 employees in the banking sector from Kampala district which was specifically chosen for this study. Appropriate analytical data tools were applied. Results reveal the presence of loan and client projections, client preparation and training, loan portfolio supervision and; mobilization and recruitment as operant competence factors that affect the performance of loans officers in the banking industry in Uganda. These findings and their policy implications are fully discussed in the paper. The research findings theoretically conceptualize employee competences from the objectivist perspective which assumes that there is an objective number of competences which an organization or a profession requires to meet its objectives and once this set has been identified, then every unit in the organization and profession works towards acquiring that set; to a new and contemporary constructivist view that allows users of the concept to define competence from their own environment. The study presents the importance of understanding these operant competences. There is a dearth of literature in addressing operant competences for bank loans officers from a Sub-Saharan context; creating a need to study and systematically document the prevailing supporting operant competences for loans officers in order to promote the banking sector in Uganda.
Keywords: Operant; Banking Sector; Loans Officer; Client; Mobilization; Training; Uganda